Healthcare-associated infections related to COVID-19 in intensive care unit patients - Rezende, Mirella Bonifácio; Silva, Arlany Micaela Sousa da; Ferreira, Bianca da Silva (Revista Prevenção de Infecção e Saúde, 2024)
Introduction: The COVID-19 pandemic, caused by the SARS-CoV-2 virus, has precipitated a global health crisis, potentially amplifying healthcare-associated infections (HAIs). Aim: To observe the impact of HAIs on COVID-19 patients admitted to the ICU of a hospital in Southern Maranhão. Design: This study is descriptive, retrospective, and quantitative, based on primary data from hospital records spanning June to November 2020. Results: The study encompassed 274 patients, with an average age of 63 years (range: 18-97 years). A low incidence of HAIs in COVID-19 patients in the ICU (2.91%) was observed during the study period. The utilization rate of invasive devices was 33.21%, with CVD (97.8%) being the predominant type. CVD-associated urinary tract infection (UTI) caused by Candida sp. accounted for 50% of diagnosed HAIs. The mortality rate attributable to HAIs in COVID-19 patients in the ICU is 1.46%, whereas the rate among those without HAIs is 25.91%. Implications: The study reveals a limited impact of HAIs on the clinical outcomes of COVID 19 patients admitted to the ICU, suggesting the need to promoting complete COVID-19 vaccination.